Transforming Adolescent Sex Offender Treatment: Organization-Wide Change Process in a State Residential Juvenile Justice System (Journal of Applied Juvenile Justice Services, 2024)
A state juvenile justice system underwent a system-wide organizational change process as a result of implementing a new empirically-based residential treatment model for adolescent sex offenders. Because of the significant differences between the new treatment model and the former, the change process required modifications in treatment philosophy and ideology, clinical practice, staff responsibilities and teamwork, and an understanding of applied research and the role of residential juvenile justice providers.  A detailed description of the transformative change process is provided and is further examined through the lens of organizational change theory.